2020
DOI: 10.1186/s13071-020-04169-0
|View full text |Cite
|
Sign up to set email alerts
|

Pan-American Trypanosoma (Megatrypanum) trinaperronei n. sp. in the white-tailed deer Odocoileus virginianus Zimmermann and its deer ked Lipoptena mazamae Rondani, 1878: morphological, developmental and phylogeographical characterisation

Abstract: Background: The subgenus Megatrypanum Hoare, 1964 of Trypanosoma Gruby, 1843 comprises trypanosomes of cervids and bovids from around the world. Here, the white-tailed deer Odocoileus virginianus (Zimmermann) and its ectoparasite, the deer ked Lipoptena mazamae Rondani, 1878 (hippoboscid fly), were surveyed for trypanosomes in Venezuela. Results: Haemoculturing unveiled 20% infected WTD, while 47% (7/15) of blood samples and 38% (11/29) of ked guts tested positive for the Megatrypanum-specific TthCATL-PCR. CAT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Molecular research on T. theileri in cattle using the abovedescribed genetic markers has suggested that phylogenetic relationships among trypanosome sequences are congruent with phylogeny based on other gene sequences (Cortez et al, 2009;Garcia et al, 2020), although the resolution degree of lineages or population diversity differs based on the gene markers assessed in relation to the inherent nucleotide conservation/divergence as well as sequencing span. Consistently, molecular studies on T. theileri indicated that the species of bovine 'T.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular research on T. theileri in cattle using the abovedescribed genetic markers has suggested that phylogenetic relationships among trypanosome sequences are congruent with phylogeny based on other gene sequences (Cortez et al, 2009;Garcia et al, 2020), although the resolution degree of lineages or population diversity differs based on the gene markers assessed in relation to the inherent nucleotide conservation/divergence as well as sequencing span. Consistently, molecular studies on T. theileri indicated that the species of bovine 'T.…”
Section: Discussionmentioning
confidence: 99%
“…4). Prior to this study, the characterization of T. trinaperronei as T. theileri-like trypanosomes in white-tailed deer across the North and Central Americans (Garcia et al, 2020) seemed reasonable, since trypanosomes of the TthII-related lineage of cervid trypanosomes ('T. cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…kinetoplast situated near the nucleus, far from the cells anterior) (Hoare, 1972). The subgenus Megatrypanum is however now restricted to those large trypanosomes found in ungulates, such as T. theileri (Garcia et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%